2015
DOI: 10.1128/aem.00127-15
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity in Swine of Orally Administered Recombinant Lactobacillus plantarum Expressing Classical Swine Fever Virus E2 Protein in Conjunction with Thymosin α-1 as an Adjuvant

Abstract: e Classical swine fever, caused by classical swine fever virus (CSFV), is a highly contagious disease that results in enormous economic losses in pig industries. The E2 protein is one of the main structural proteins of CSFV and is capable of inducing CSFVneutralizing antibodies and cytotoxic T lymphocyte (CTL) activities in vivo. Thymosin ␣-1 (T␣1), an immune-modifier peptide, plays a very important role in the cellular immune response. In this study, genetically engineered Lactobacillus plantarum bacteria exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Samples of the intestinal tract were stored at − 40 °C until analysis. In addition, fecal samples were collected on days 0, 4, 6,8,10,12,14,16,20,22,24,26,28,30,32,34, and 36 after immunization, and treated according to a previously described method [26]. Briefly, 0.1 g of fecal pellets were suspended in 400 μL of PBS containing 1 mmol L −1 phenylmethylsulfonyl fluoride (Sigma, USA) and 1% bovine serum albumin (BSA), and then incubated at 4 °C for 16 h. After centrifugation, the supernatants were stored at − 40 °C until use.…”
Section: Specimen Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of the intestinal tract were stored at − 40 °C until analysis. In addition, fecal samples were collected on days 0, 4, 6,8,10,12,14,16,20,22,24,26,28,30,32,34, and 36 after immunization, and treated according to a previously described method [26]. Briefly, 0.1 g of fecal pellets were suspended in 400 μL of PBS containing 1 mmol L −1 phenylmethylsulfonyl fluoride (Sigma, USA) and 1% bovine serum albumin (BSA), and then incubated at 4 °C for 16 h. After centrifugation, the supernatants were stored at − 40 °C until use.…”
Section: Specimen Collectionmentioning
confidence: 99%
“…Cell wall associated or secreted factors from some Lactobacillus strains can enhance innate immune responses and epithelial barrier function, modulate the intestinal micro-environment, regulate immune cell behavior, and elicit release of cytokines [11]. In addition to natural immune-stimulating adjuvants with weak immunogenicity [12] and capacity to survive the gastric acid and digestive enzymes, several Lactobacillus strains have been applied for the delivery of heterologous antigens to trigger mucosal immune responses against pathogens [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in animal models have found that antigen delivery by orally administered L. plantarum may elicit secretion of specific IgA antibodies against antigens related to influenza (61), cancer (44), foot-and-mouth disease virus (FMDV) (62), and classical swine fever virus (63). In this regard, we investigated whether orally administered AgE6-displaying L. plantarum induced production of AgE6-specific IgA antibodies at intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…There were three LAB adjuvant studies that did not fit into the above categories: Japanese herbal medicines (Juzen-taiho-to (JTT) and Hochi-ekki-to (HEY)), receptor activator of nuclear factor kappa-B ligand (RANKL), and thymosin α-1 [116][117][118]. They are briefly reviewed in Table 5 and their mechanisms of action described here.…”
Section: Other Adjuvant Strategiesmentioning
confidence: 99%